Peramalan Produksi Perikanan Laut di Provinsi Jawa Tengah: Pendekatan Statistik dan Machine Learning - Amnur, Muh. Alfian; Pramana, Setia (Seminar Nasional Official Statistics, 2025)
Fisheries production in Central Java Province experiences seasonal fluctuations that affect supply stability and fishermen's income. This study aims to analyze the production trends from 2013 to 2023 and compare the performance of the SARIMA and Random Forest models in forecasting fishery production sold at Fish Auction Sites (TPI). Based on evaluation metrics including MAE, RMSE, and MAPE, the SARIMA(8,1,1)(1,1,0)[12] model demonstrated the best performance with values of 2930.12, 3749.83, and 15.40, respectively. Additionally, the SARIMA model was used to forecast production for January 2024, resulting in an estimated output of 26,210.63 tons. This forecast is expected to assist stakeholders in monitoring fishery production in Central Java Province.